Conversational Implicature Between Students in Deutsch Für Tourismus With Rollenspiel Technique - Harahap, Herlina Jasa Putri; Reza, Muhammad (Nusantara Science and Technology Proceedings)
This research examined the violation of the principle of cooperative conversation with data sources from conversations among students in the course Deutsch für Tourismus with a learning model using the Rollenspiel teaching method. Besides aiming to describe and categorize forms of violation of the principle of cooperative conversation, this study also aimed to describe the types of conversational implicatures that arise from violations of the principle of cooperative conversation. The method used is a qualitative method with descriptive elaboration using the theory of the principle of cooperative conversation by Grice and the theory of conversational implicatures by Yule. Based on the analysis found 25 utterances containing violations of the principle of cooperative conversation. Violations of the principle of cooperative conversation include violations of the maxim of quantity with 8 data, violations of the maxim of quality with 6 data, violations of the maxim of relevance with 8 data, and violations of the maxim of manner with 3 data. The conversations among students, it contains often more information than is needed and does not provide relevant contributions. Three types of conversational implicatures arise from the violation of the principle of cooperative conversation, namely: 5 types of general conversational implicatures, 2 types of scaled conversational implicatures and the dominant ones are the specific conversational implicatures with a total of 21 because the conversations among students occur often requires special knowledge in understanding the context.